2020
DOI: 10.1073/pnas.1917635117
|View full text |Cite
|
Sign up to set email alerts
|

A precisely positioned MED12 activation helix stimulates CDK8 kinase activity

Abstract: The Mediator kinase module regulates eukaryotic transcription by phosphorylating transcription-related targets and by modulating the association of Mediator and RNA polymerase II. The activity of its catalytic core, cyclin-dependent kinase 8 (CDK8), is controlled by Cyclin C and regulatory subunit MED12, with its deregulation contributing to numerous malignancies. Here, we combine in vitro biochemistry, cross-linking coupled to mass spectrometry, and in vivo studies to describe the binding location of the N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 59 publications
2
62
4
1
Order By: Relevance
“…Biochemical studies suggested that the N terminus of MED12, which is a hot spot for oncogenic mutations (Makinen et al 2011;Lim et al 2014), interacted with CCNC as part of the MED12-dependent activation mechanism (Turunen et al 2014). However, these findings were contradicted by CXMS data obtained with partial assemblies of the human CDK8 module (Klatt et al 2020). The CXMS results supported an interaction between the MED12 N terminus (residues 30-42) and a disordered CDK8 activation loop (residues 173-203).…”
Section: Mediator Kinase Modulementioning
confidence: 77%
See 1 more Smart Citation
“…Biochemical studies suggested that the N terminus of MED12, which is a hot spot for oncogenic mutations (Makinen et al 2011;Lim et al 2014), interacted with CCNC as part of the MED12-dependent activation mechanism (Turunen et al 2014). However, these findings were contradicted by CXMS data obtained with partial assemblies of the human CDK8 module (Klatt et al 2020). The CXMS results supported an interaction between the MED12 N terminus (residues 30-42) and a disordered CDK8 activation loop (residues 173-203).…”
Section: Mediator Kinase Modulementioning
confidence: 77%
“…Similar activation loops (also known as T-loops) exist in other CDKs, but the CDK8 sequence contains a D instead of a typical T at residue 191, suggesting a phosphorylation-independent activation mechanism. The MED12 N terminus (residues 19-50) is predicted to adopt an α-helical structure, and a model was proposed in which negatively charged residues (e.g., E33) in this MED12 "activation helix" mimicked CDK8 activation loop phosphorylation as a means to activate CDK8 (Klatt et al 2020). The structural discrepancies between these models for MED12-dependent activation of CDK8 could reflect two distinct mechanisms of activation.…”
Section: Mediator Kinase Modulementioning
confidence: 99%
“…Completing the kinase module are: cyclin C (CCNC), and subunits MED12 and MED13. CDK8/19 activity appears restricted by its requirement for proper quaternary structure [ 23 ]. For full activity, CDK8/19 must associate simultaneously with cyclin C and with MED12, the latter embraces CDK8 allowing it to attain proper opening of its T-loop [ 23 ].…”
Section: Mediator: a Bridge Between Enhancers And Promotersmentioning
confidence: 99%
“…CDK8/19 activity appears restricted by its requirement for proper quaternary structure [ 23 ]. For full activity, CDK8/19 must associate simultaneously with cyclin C and with MED12, the latter embraces CDK8 allowing it to attain proper opening of its T-loop [ 23 ]. Evidence suggests that only CDK8, or CDK19, can occupy Mediator at one time, and the same is true for the paralog subunits MED12L and MED13L (reviewed elsewhere) [ 8 , 9 , 22 ].…”
Section: Mediator: a Bridge Between Enhancers And Promotersmentioning
confidence: 99%
See 1 more Smart Citation